International Classification for Industrial Designs Locarno Classification - World Intellectual Property Organization (Geneva, Switzerland WIPO, 2012)
The Locarno classification established under the Locarno Agreement consists of a classification for industrial designs. It comprises a list of 32 classes and 219 subclasses with explanatory notes and an alphabetical list of goods in which industrial designs are incorporated, with an indication of the classes and subclasses into which they fall. This list contains some 7,024 indications of different kinds of goods. In order to keep the Locarno Classification up to date, it is continuously revised and a new edition is published every five years. La clasificación de Locarno establecida en virtud del Arreglo de Locarno consiste en una clasificación para diseños industriales. Comprende una lista de 32 clases y 219 subclases con notas explicativas y una lista alfabética de los productos en los que se incorporan los diseños industriales, con indicación de las clases y subclases a las que pertenecen. Esta lista contiene unas 7.024 indicaciones de diferentes tipos de mercancías. Para mantener la Clasificación de Locarno actualizada, se revisa continuamente y se publica una nueva edición cada cinco años.
The ninth edition will be in force as from January 1, 2009 and will replace the previous edition.
Keywords: CLASIFICACION - BIBLIOGRAFICA -- LOCARNO -- DISEÑOS INDUSTRIALES